Baseline prevalence and incidence and risk factors for new-onset drug induced hearing loss in adults receiving drug-resistant tuberculosis (DR-TB) treatment in Khayelitsha, South Africa - Njuguna, Christine Wanjiku (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references.